Aquatic and Dry Land Weeds as Potential Renewable Fibers Resources for Paper - Tamrin Tamrin; Filli Pratama; Rahmad Hari Purnomo; Nessia Davitri (Program Pascasarjana Universitas Sriwijaya, 2017)
Abstract: The investigation of aquatic and dry land weeds as fibers resources for paper making was carried out. The selected fiber resources of aquatic weeds were water hyacinth (Eicchornia crassipes) and water chestnuts (Eleocharis dulcis), and bladygrass (Imperata cylindrica) as the selected dry land weed. Research was designed as a factorial completely randomized design with two factors. The first factor was fibers origin (Eicchornia crassipes, Imperata cylindrica, Eleocharis dulcis) and the second factor was the fibers pulp slurry concentrations (30%, 50%, and 70% v/v). Results showed that the fibers origin and fibers pulp slurry concentration had significant effect on the tensile strength, mass density, water absorption, and frictional resistance of paper. The interaction between the fibers origin and fibers pulp slurry concentration had significant effect on tensile strength, frictional resistance, water absorption; but had no significant effect on mass density of paper. The paper that was made of 70% (v/v) of water hyacinth fiber pulp slurry showed the best characteristics with the tensile strength of 3.65 kgf mm-1, mass density of 0.87 g cm-3, water absorption of 0.235 g cm-2, and frictional resistance of 0.028 g cm-2.Keywords: water hyacinth, water chestnuts, bladygrass, paper.Abstrak (Indonesian): Penelitian tentang sumber serat dari gulma air dan lahan kering untuk pengolahan kertas telah dilakukan. Gulma air yang potensial sebagai sumber serat adalah eceng gondok (Eicchornia crassipes) dan purun tikus (Eleocharis dulcis); alang-alang (Imperata cylindrica) sebagai sumber serat dari gulma lahan kering. Penelitian ini menggunakan rancangan acak lengkap yang disusun secara factorial dengan dua faktor. Faktor pertama adalah jenis gulma (Eicchornia crassipes, Imperata cylindrica, Eleocharis dulcis) dan faktor ke dua adalah konsentrasi penambahan bubur serat (30%, 50%, and 70% v/v). Hasil penelitian menunjukkan bahwa jenis gulma dan konsentrasi penambahan bubur serat berpengaruh nyata (p<0.05) terhadap kekuatan tarik, massa jenis, absorpsi air dan ketahanan gesek. Interaksi antara jenis gulma dan konsentrasi penambahan bubur serat berpengaruh nyata terhadap kekuatan tarik, ketahanan gesek, abosrpsi air; tetapi berpengaruh tidak nyata terhadap massa jenis kertas. Kertas yang dibuat dari serat eceng gondok dengan konsentrasi bubur serat sebanyak 70% (v/v) menghasilkan kertas dengan sifat mekanik dan fisik terbaik dengan kekuatan tarik 3,65 kgf mm-1, massa jenis 0,87 g cm-3, absorpsi air 0,235 g cm-2, dan ketahanan gesek 0,028 g cm-2.Katakunci: eceng gondok, purun tikus, alang-alang, kertas.